A Study of the Prevalence of Psychiatric Disorders in‏ ‏Patients with ‎Methamphetamine-Induced Psychosis - Mahin Eslami-Shahrbabaki; Alireza Fekrat; Shahrzad Mazhari (Addiction and Health, 2015)
Background: The abuse of narcotic drugs and psychotropic substances such as amphetamines and ecstasy has had a growing trend. Tachycardia, increased blood pressure, hallucinations, panic attacks, and psychosis are the negative effects of methamphetamine abuse. The present study aimed to assess psychiatric disorders associated with methamphetamine-induced psychotic disorder. Methods: This cross-sectional study was performed from October 2013 to March 2014 on 165 patients hospitalized at Shahid Beheshti Hospital in Kerman, Iran, and diagnosed with psychosis induced by methamphetamine abuse within the previous 6 months. Study subjects were selected via census method. Based on the exclusion criteria and due to the lack of cooperation of some patients, 121 patients were enrolled in the study. Research data were gathered using clinical interviews, the Yale-Brown obsessive compulsive scale (Y-BOCS), Hamilton anxiety scale (HAM-A) and Hamilton rating scale for depression (HRSD), Young mania rating scale (YMRS), substance dependence severity scale (SDSS), positive and negative syndrome scale (PANSS), and clinical global impression (CGI) scale. The data analysis was performed using SPSS software, descriptive statistics, and ANOVA. Findings: Among the 121 patients of the sample group, 4 patients (3.3%) had anxiety, 58 patients (47.9%) depression, 30 patients (24.8%) obsessive-compulsive disorder (OCD), 20 patients (16.5%) bipolar mood disorder (BMD), 8 patients (6.6%) persistent psychotic symptoms, 85 patients (70.2%) personality disorder, and 36 patients (29.8%) had no personality disorders. The highest prevalence was related to borderline personality disorder (35.5%). However, 45 patients (37.2%) had no impairment associated with methamphetamine-induced psychosis. Conclusion: It seems that there is comorbidity between psychiatric disorders, including mood disorders, especially depressive disorder, childhood history of attention deficit hyperactivity disorder (ADHD), bipolar disorder, and personality disorders such as borderline personality disorder, and antisocial personality disorders, and methamphetamine abuse.